P46 Dextrocardia and right atrial isomerism associated with congenital trifurcation of trachea. (2nd March 2016) - Zafar, A; Williamson, M
Abstract : Background: A 34 weeks gestation baby was born with complex cardiac congenital heart disease i.e. dextrocardia, right atrial isomerism and moderate pulmonary stenosis. The baby was ventilated because of prematurity and poor respiratory effort. However, later on during the course, the baby failed multiple attempts at extubation. Case Report: This is about a white Caucasian female who was born at 34 weeks. She had antenatal diagnosis of right atrial isomerism, dextrocardia and asplenia. Postnatally, she had moderate pulmonary stenosis. Her pulmonary flow was moderately reduced necessitating a BT shunt earlier on. She was ventilated from birth due to prematurity and poor respiratory effort however a few weeks later, an attempt to extubate her failed. Multiple attempts at extubation later on were unsuccessful. This prompted a flexible bronchoscopy which showed trifurcation of trachea. This included a morphological right bronchus and two left bronchus. One of the left bronchus ended in a blind loop. There was moderate tracheomalacia as well. A tracheostomy was eventually performed for respiratory support. In the course of time, pulmonary flow deteriorated again due to supravalvular and valvular stenosis of undetermined aetiology. Hence a right ventricular to pulmonary artery conduit was performed. Discussion: Trifurcate trachea is very rare and its association with pulmonary artery stenosis was unrelated in our case but it is important to look for structural and functional association of trifurcate trachea with pulmonary artery narrowing.